AEROBIC EXERCISE PERFORMED IN ADULT LIFE MAINTAINS BODY WEIGHT AND FOOD INTAKE OF MALE RATS EVEN AFTER TRAINING INTERRUPTION - Marcos Vinícius Martins; Leticia Ferreira Barbosa; Scarlett Rodrigues Raposo; Maria Natalia C. Peres; Gabriel Kian G. Lopes; Maryana D. Fernandes; Kerolym L. da Cruz; Rafael P. Lopes; Veridiana Mota Moreira; Paulo Cezar de Freitas Mathias (Arquivos do Mudi, 2023)
Excess weight in adult life is an important risk factor for the development ofnoncommunicable diseases. On the other hand, aerobic physical exercise programs have beenshown to be important components both in the prevention and control of these conditions.This work aims to evaluate the effects of moderate intensity training on the body weight(BW) and food intake (FI) of adult male rats. Wistar rats were obtained at 30 days old.Throughout the experimental period, they were kept in appropriate cages (4 rats per box)containing food and water, temperature (22ºC) and photoperiod (07:00 to 19:00) controlled.At PN 40 they were divided into sedentary (S) and exercised (E) groups. The BW and FI weremeasured twice a week, from 40 to 140 days old. Exercised rats performed a moderate-intensity treadmill running from PN 90 to 120. During this period, they were submitted to aneffort test to evaluate performance and control the training load (55% to 65% VO 2max ). Theresults showed that both BW and FI were not altered with the training performed during adultlife, even after 20 days of exercise cessation. More studies are needed in order to assesswhether moderate-intensity training is able to attenuates the deleterious effects observed inthe biometric and metabolic markers of adult rats programmed for obesity and/or metabolicsyndrome.